2012
DOI: 10.4161/fly.19249
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and neurobiology of aggression in Drosophila

Abstract: Aggressive behavior is widely present throughout the animal kingdom and is crucial to ensure survival and reproduction. Aggressive actions serve to acquire territory, food, or mates and in defense against predators or rivals; while in some species these behaviors are involved in establishing a social hierarchy. Aggression is a complex behavior, influenced by a broad range of genetic and environmental factors. Recent studies in Drosophila provide insight into the genetic basis and control of aggression. The sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 147 publications
(290 reference statements)
0
54
0
1
Order By: Relevance
“…During courtship, male flies emit songs via wing vibrations, tap and lick (Yamamoto and Koganezawa, 2013). The presence of females may also incite aggression among males, causing them to posture, lunge and box (Zwarts et al, 2012). Therefore, it is likely that courting or fighting males would transiently become tightly linked with courted females or sparring partners in mixed-sex SINs.…”
Section: As Simple As Possible But Not Simplermentioning
confidence: 99%
“…During courtship, male flies emit songs via wing vibrations, tap and lick (Yamamoto and Koganezawa, 2013). The presence of females may also incite aggression among males, causing them to posture, lunge and box (Zwarts et al, 2012). Therefore, it is likely that courting or fighting males would transiently become tightly linked with courted females or sparring partners in mixed-sex SINs.…”
Section: As Simple As Possible But Not Simplermentioning
confidence: 99%
“…In invertebrates, serotonin (5HT), nitric oxide (NO) and selected peptides affect the tendency to flee, avoiding further contests 10,42 . To date, relatively few model systems have been developed to shed light on how previous experience modifies aggressive behaviour in arthropods, mainly crickets 26 , drosophilid flies 43 and ants 28 (see also recent reviews 4,9,22,44 ). We propose a new model system, the olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae).…”
mentioning
confidence: 99%
“…A Wolbachia strain has been shown previously to disrupt the biosynthesis of insect neurotransmitters (35). Drosophila male aggression is highly influenced by the monoamine neurotransmitter octopamine (43). Alterations to OCT have been shown to reduce aggressive latency in male Drosophila (49).…”
Section: Resultsmentioning
confidence: 99%
“…All fighting pairs had the same Wolbachia infection status, i.e., between infected or uninfected pairs. Studies have found that socially naive flies are more aggressive than individuals exposed to other flies (43); therefore, male pupae were isolated before eclosion. Twenty pairs of wMelCS-, wMel-, and wMelPop-infected males and their genetically paired Wolbachia-free lines (n ϭ 20; 40 males per fly line, for a total of 240 males) were collected as pupae 1 day prior to eclosion and isolated in individual vials containing standard food medium for the remainder of their rearing period.…”
Section: Methodsmentioning
confidence: 99%